Latin Motets I - Byrd, William 1539/40-1623; Edwards, Warwick; Brett, Philip (London Stainer & Bell New York Galaxy Music Corp., 1984)
This volume is devoted to Byrd’s Latin sacred works which have survived only in manuscript sources. Its contents range from those motets such as Alleluya. Confitemini Domino judged to be among the composer’s earliest, to works of the 1560s – Ad Dominum cum tribularer for example – and two later cantus firmus respond motets that may also be dated to this period.
from manuscript sources
Keywords: 16th Century (1501-1600); Motet